Answer:
Length: 25
Width: 9
Step-by-step explanation:
A^2 = b^2 + c^2 - 2bc cos a
= 11^2 + 5^2 - 2*5*11 cos 40
= 7.86 to 2 DP's
to find the remaining angles use the sine rule:-
a / sin A = b / sin B so
7.857/ sin 40 = 11 / sin B
sin B = 11 sin40 / 7.857 = 0.8999
<B = 64 degrees
so <C = 180 - 64-40 = 76 degrees
Answer:
So, the relation between variables are
![y=\frac{x^4}{7}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7Bx%5E4%7D%7B7%7D)
Step-by-step explanation:
We are given
![\frac{x^4}{y}=7](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E4%7D%7By%7D%3D7)
Since, we have to find relation between variables
so, we can solve for y
![\frac{x^4}{y}=7](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E4%7D%7By%7D%3D7)
Firstly, we will multiply both sides by y
![\frac{x^4}{y}\times y=7\times y](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E4%7D%7By%7D%5Ctimes%20y%3D7%5Ctimes%20y)
we can simplify it
![x^4=7\times y](https://tex.z-dn.net/?f=x%5E4%3D7%5Ctimes%20y)
we can isolate y
so, we can divide both sides by 7
so, we get
![y=\frac{x^4}{7}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7Bx%5E4%7D%7B7%7D)
Answer:
y = 2x
y = 3x - 3
Step-by-step explanation:
Hi,
<u>y = 2x</u>
<u>6 = 2(3)</u>
<u>6 = 6</u>
<u>That's a solution</u>
<u>y = 3x - 3</u>
<u>6 = 3(3) - 3</u>
<u>6 = 9 - 3</u>
<u>6 = 6</u>
<u>That's a solution</u>
Hope this helps :)